Respostas
respondido por:
2
a1 = 2
a2 = 4
Razão r = a1 - a1 = 4 - 2 = 2
Soma: Sn = (a1 + an).n/2
2550 = (2 + an).n/2
5100 = 2n + an.n
(5100 - 2n)/n = an (1)
Termo geral: an = a1 + (n - 1).r
(5100 - 2n)/n = 2 + (n - 1).2
(5100 - 2n)/n = 2 + 2n - 2
(5100 - 2n)/n = 2n
5100 - 2n = 2n²
2n² + 2n - 5100 = 0 (÷2)
n² + n - 2550 = 0
Δ = (1)² - 4(1)(-2550)
Δ = 1 + 10200 = 10201
√Δ = √10201 = 101
n = (-1 + 101)/2 = 100/2 = 50
n = (-1 - 101)/2 = -102/2 = -51 (não serve)
Substituindo n em (1), temos:
(5100 - 2n)/n = an
a50 = (5100 - 2.50)/50
a50 = 5000/50
a50 = 100
Resposta: an = 100
Espero ter ajudado.
a2 = 4
Razão r = a1 - a1 = 4 - 2 = 2
Soma: Sn = (a1 + an).n/2
2550 = (2 + an).n/2
5100 = 2n + an.n
(5100 - 2n)/n = an (1)
Termo geral: an = a1 + (n - 1).r
(5100 - 2n)/n = 2 + (n - 1).2
(5100 - 2n)/n = 2 + 2n - 2
(5100 - 2n)/n = 2n
5100 - 2n = 2n²
2n² + 2n - 5100 = 0 (÷2)
n² + n - 2550 = 0
Δ = (1)² - 4(1)(-2550)
Δ = 1 + 10200 = 10201
√Δ = √10201 = 101
n = (-1 + 101)/2 = 100/2 = 50
n = (-1 - 101)/2 = -102/2 = -51 (não serve)
Substituindo n em (1), temos:
(5100 - 2n)/n = an
a50 = (5100 - 2.50)/50
a50 = 5000/50
a50 = 100
Resposta: an = 100
Espero ter ajudado.
ProfRafael:
Obrigado!
respondido por:
0
Resposta: =100
Explicação passo a passo:
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás